SOUTHWEST TECHNOLOGICAL PARK OF SÃO PAULO: DRIVING FACTOR OF THE PROSPECTIVE PROCESS FOR TERRITORIAL DEVELOPMENT (Gestão & Regionalidade, 2018)
Considering that technological parks must attend regions, societies and countries necessities, this work aims to present the strategic planning of the Technological Park of Southwest São Paulo (PTSP), its organizational structure and pedagogical-political project, and the difficulties for its deployment in the poorest region of São Paulo. The park appears as a result of the prospective process, with society appropriation, developed in the municipality of Ribeirão Branco (southwest of São Paulo state), and the chosen methodology is one of exploratory approach and action-research. The results show that the appropriation by the society, such as its participation in the prospective process of the region development, are essential for the advancement of the PTSP, which will positively impact on the society, creating greater business and job opportunities, and reducing emigration of young people from Ribeirão Branco. Keywords: Technology park; prospective process; strategic planning; territorial development; sustainable development.